Risk Factors Associated with Structural Progression in Normal-Tension Glaucoma: Intraocular Pressure, Systemic Blood Pressure, and Myopia - Lee, Kwanghyun (Invest Ophthalmol Vis Sci, 2020)
PURPOSE: To determine risk factors associated with structural progression in medically treated normal-tension glaucoma (NTG). METHODS: This retrospective cohort study included 166 NTG patients (average age, 56.5 years; average mean deviation, −4.2 dB). The structural progression endpoint was determined by optical coherence tomography; significant thickness differences in the peripapillary retinal nerve fiber layer (RNFL) or macular ganglion cell inner plexiform layer (GCIPL) that exceeded baseline test-retest variability were identified with event-based guided-progression analysis. Intraocular pressure and systemic blood pressure (BP) were measured at each visit throughout the follow-up period, and the risk for progression was evaluated with Cox regression. Myopic disc features and antihypertensives were also analyzed. Tree analysis was used to determine the cutoff values and elucidate influential risk factors. RESULTS: Structural progression, defined as progressive peripapillary RNFL or macular GCIPL thinning, was identified in 62 eyes. Occurrence of disc hemorrhages, presence of diabetes, and lower minimum systolic BP were associated with progression (hazard ratio [HR]: 2.116, P = 0.005; HR: 1.998, P = 0.031; HR: 0.968, P = 0.005; respectively). The cutoff value derived from the tree analysis of minimum systolic BP was 108 mm Hg. The tree analysis revealed systolic and diastolic BP to be the most influential risk factors for progressive peripapillary RFNL thinning and progressive macular GCIPL thinning, respectively. CONCLUSIONS: Low BP measured during follow-up correlated with structural progression in medically treated NTG eyes, indicating that the evaluation of hypotension is required during the management of NTG patients. The tree analysis identified BP target values that may help prevent glaucoma progression.